Assessment of fish quality: the Quality Index Method versus HPLC analysis in Sarda sarda (Bloch, 1793). (29th March 2019) - Anacleto, Patrícia; Barbosa, Vera; Maulvault, Ana; Rosa, Rui; Leonor Nunes, Maria; Marques, António; Paulo Noronha, João; Sousa Diniz, Mário
Abstract : Introduction: Nowadays, the evaluation of the quality of food products is fundamental to strengthen the confidence of consumers. The Quality Index Method (QIM) and analytical methodologies (e.g. HPLC, LC-MS-MS, GC-MS) are essential to ensure seafood quality and to prevent the marketability of unsafe products. Usually, the most common techniques are based on the determination of biogenic amines (BA) in seafood samples [1, 2 ]. The main objective of the present study was to develop a sensory classification scale of seafood quality and cross-check the results with BA using Sarda sarda, an Atlantic Scombridae, as model organism. Materials and methods: Seafood samples of fresh Sarda sarda purchased from national retailers were exposed for 13 days to controlled temperature. Afterwards, samples were daily collected for analysis. Fish samples were analyzed by the Quality Index Method (QIM) using a sensory classification scale, based on traditional organoleptical methodologies of seafood quality, and by HPLC for target biogenic amines as previously described [3–5 ]. Results and discussion: Immediately after one day of exposure, the quality assessment through QIM registered a decrease of fish freshness, becoming more pronounced in the following two days of exposure. As expected, over time the quality of fish analyzed deteriorated significantly. However, the results from HPLC analysis showed that in the beginning (T0), putrescine was already detected, and after five days, other biogenic amines emerged, such as histamine, tyramine, cadaverine and agmatine. Conclusions: In conclusion, fish had good quality at the time of purchase, and it was confirmed that QIM is a quick and reliable evaluation of seafood quality as far as biogenic amines are concerned.